Origins and phylogeny of rices - Nayar, N. M. (Oxford, UK : Elsevier Science, 2014)
Origin and Phylogeny of Rices provides an evolutionary understanding of the origin, spread, and extent of genetic diversity in rice. This single volume is the first to review and synthesize the significant work done in this area in the last 30 years. Rice is the most important food crop of humankind. It provides more energy and also forms the staple food for more humans than any other food plant. This book assesses multiple aspects of this crucial crop in chapters devoted to rice's history and spread, phylogeny of the genus Oryza, Oryza species and their interre.
4. THE HOLOCENE CLIMATE IN SOUTH SAHARA AND THE SAHEL5. THE HISTORY OF AFRICAN RICE; 6. EAST AFRICA AND MADAGASCAR; 7. THE RICE ARCHAEOLOGY OF AFRICA; 8. RICE CULTURE IN WEST AFRICA; 9. WILD RICES OF AFRICA; 10. CHARACTERISTICS OF AFRICAN RICE; 11. THE FALL OF AFRICAN RICE; 12. THE GENETIC TRANSFORMATION OF AFRICAN RICE; 13. THE ORIGIN OF AFRICAN RICE; 14. TIME AND PLACE OF ORIGIN; Chapter 6 -- The Origin of Asian Rice; 1. INTRODUCTION; 2. PAST STUDIES; 3. LATE PLEISTOCENE-HOLOCENE CLIMATE; 4. ARCHAEOLOGICAL STUDIES; 5. ORIGIN AND EVOLUTION; EPILOGUE; REFERENCES; INDEX.
PDF (ScienceDirect, viewed on July 2, 2014).
Includes bibliographical references and index.
Keywords: Rice -- Biotechnology; Rice -- History; Rice; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science; Rice; Rice -- Biotechnology; Electronic books; History